2015
DOI: 10.5964/ejop.v11i4.991
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Markers of Processing Trauma Experience in Women’s Written Narratives During Different Breast Cancer Phases: Implications for Clinical Interventions

Abstract: Research into the change processes underlying the benefits of expressive writing is still incomplete. To fill this gap, we investigated the linguistic markers of change in cognitive and emotional processing among women with breast cancer, highlighting the differences and peculiarities during different treatment phases. A total of 60 writings were collected from 20 women: 10 receiving chemotherapy and 10 receiving biological therapy. We performed a series of repeated measures ANOVA for the most meaningful LIWC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…We explain that people with traumatic experiences have more empathy than the control group because they have suffered misfortunes. Unlike previous studies (Martino, Onorato, & Freda, ), our study found the CSA group was less likely to mention negative emotional and anxiety words. And the former also mentioned that the CSA group tended to have less verbal expression including emotional words expression.…”
Section: Discussioncontrasting
confidence: 99%
“…We explain that people with traumatic experiences have more empathy than the control group because they have suffered misfortunes. Unlike previous studies (Martino, Onorato, & Freda, ), our study found the CSA group was less likely to mention negative emotional and anxiety words. And the former also mentioned that the CSA group tended to have less verbal expression including emotional words expression.…”
Section: Discussioncontrasting
confidence: 99%
“…A diagnosis of breast cancer is considered a potential traumatic event associated with physical and psychological effects (Martino et al, 2013, 2015; Villani et al, 2016) that may also occur after the end of medical treatments (Cordova et al, 2007; Elklit and Blum, 2011). Cancer has a specific and peculiar nature because of the difficulty of recognizing a unique stressful.…”
Section: Introductionmentioning
confidence: 99%
“…Within a socio-constructivist and semiotic perspective, (Salvatore and Freda, 2011; Valsiner, 2014; Salvatore, 2016) the traumatic condition is due to the sudden and unexpected alteration of basic elements governing the relation between women and the external world (Janoff-Bulman, 2004; Joseph and Linley, 2005) and rupture of the temporal continuity resulting in a crisis of meaning processes that support the personal self-narrative of life (Brockmeier, 2000; Neimeyer, 2004, 2006; Martino et al, 2015; Carlino and Margherita, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a traumatic stressor for younger women because it is often more aggressive, lethal and destructive to daily life and to their own vision of the world (Yazdani-Charati et al, 2019). Women under the age of 50 show more emotional distress, anxiety, and depression symptoms and lower vigour for aggressiveness of chemotherapy received, regardless of the surgical procedure or tumour evaluation time (Martino et al, 2015; Mosher and Danoff-Burg, 2006). Studying the potential traumatic nature of breast cancer, Cordova et al (2007) showed that age is inversely associated with the perception of a positive change after cancer (Bower et al, 2005; Manne et al, 2004).…”
Section: Introductionmentioning
confidence: 99%